2020
DOI: 10.17218/hititsosbil.728146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Covid-19 Outbreak on Turkish Stock Market: A Sectoral-Level Analysis

Abstract: The Novel Coronavirus has brought uncertainties to all countries in the world, causing human suffering and economic downturn that are unprecedented in recent history. This paper is the first empirical research that analyzes the effects of the outbreak on the Turkish stock market. The paper employed a fixed-effect model with daily data to explore the economic impact of the global pandemic at the sectoral level. Findings showed that sectoral indices were affected by the number of cases reported in Turkey than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The powerful impact on the pandemic towards financial stock market also has been highlighted by Baker, Bloom, Davis, Kost, Sammon and Viratyosin (2020) where the government restrictions in a services-oriented economy was the main factor of U.S stock market reacted unprecedented to Covid-19 compared to the previous pandemic happened in 1918-19,1957-58 and 1968. Ozturk, Sisman, Uslu and Citak (2020 found that sectoral indices in turkey were significantly affected by the global Covid-19 cases number and more specifically in sectors such metal products, machinery and sports, insurance and banking sector.…”
Section: Literature Reviewmentioning
confidence: 92%
“…The powerful impact on the pandemic towards financial stock market also has been highlighted by Baker, Bloom, Davis, Kost, Sammon and Viratyosin (2020) where the government restrictions in a services-oriented economy was the main factor of U.S stock market reacted unprecedented to Covid-19 compared to the previous pandemic happened in 1918-19,1957-58 and 1968. Ozturk, Sisman, Uslu and Citak (2020 found that sectoral indices in turkey were significantly affected by the global Covid-19 cases number and more specifically in sectors such metal products, machinery and sports, insurance and banking sector.…”
Section: Literature Reviewmentioning
confidence: 92%
“…There are also studies in the literature examining the impact of the Covid-19 pandemic on Turkish financial markets (Kandil Göker et al, 2020;Öztürk et al, 2020;Tayar et al, 2020;Kılıç, 2020;Özdemir, 2020;Korkut et al, 2020). Kandil Goker et al (2020 found that the highest decreases in the Covid-19 period were in the Sports, Tourism and Transport indices.…”
Section: Article In Press -Corrected Proofmentioning
confidence: 99%
“…Recent studies show that the pandemic (COVID-19) had an unprecedently detrimental impact on both households and firms, inducing a recession also referred to as the Great Lockdown (Kithiia et al ., 2020; Öztürk et al ., 2020; Shafi et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%